Cross Sectional and Epidemiological Studies of Bovine Babesiosis in Two Types of Geographical Regions of Andhra Pradesh, India: RESEARCH PAPER - Patteda Dhanamjayan; Bhavanam Sudhakara Reddy; Bollam Shobhamani; Sirigireddy Sivajothi (Annals of Arid Zone, 2025)
The goal of the current study was to document the prevalence of bovine babesiosis in cattle across two different geographical regions of Andhra Pradesh from January 2023 to December 2024 and to assess the factors responsible for variations. Microscopic examination of stained blood smears revealed that overall prevalence of babesiosis was 21.87%, while the polymerase chain reaction assay, which targeted the 18s rRNA gene by creating an amplified product of 733 bp, revealed an overall prevalence of 38.54%. By microscopy, the highest prevalence of babesiosis was observed in Chittoor district (31.25%) compared to YSR Kadapa district of Andhra Pradesh (12.50%). By PCR, the prevalence was 22.08% in YSR Kadapa district and 55.00% in Chittoor district. The highest prevalence of babesiosis was recorded in Chittoor district, where the number of migratory cattle moving between the borders of Andhra Pradesh, Tamil Nadu, and Karnataka is high. In contrast, YSR Kadapa district has predominantly static cattle, which showed a lower prevalence of babesiosis. This may be a consequence of sudden climatic shifts in the two locations where cattle are frequently transported across state borders. The higher prevalence could also be attributed to farmers importing a greater number of purebred cattle. In addition, unauthorized cattle sales and purchases at border areas, along with inadequate health inspections by authorities prior to interstate transportation, may further contribute to the increased prevalence.